The International Bank and World Trade - McCloy, John J. (World Bank, Washington, DC, 2019)
John J. McCloy, President of the International Bank for Reconstruction and Development, spoke about the loans granted by the Bank for European reconstruction and trade promotion. The Bank is currently in discussions about development projects for more than 20 member countries. He noted the shortage of technical experts in under-developed countries. Financial stability is necessary for trade growth. He concluded by saying that a prosperous world would be possible only if there was a good volume of international trade.